2020
DOI: 10.3390/ijms21186868
|View full text |Cite
|
Sign up to set email alerts
|

Tricarboxylic Acid Cycle Metabolites as Mediators of DNA Methylation Reprogramming in Bovine Preimplantation Embryos

Abstract: In many cell types, epigenetic changes are partially regulated by the availability of metabolites involved in the activity of chromatin-modifying enzymes. Even so, the association between metabolism and the typical epigenetic reprogramming that occurs during preimplantation embryo development remains poorly understood. In this work, we explore the link between energy metabolism, more specifically the tricarboxylic acid cycle (TCA), and epigenetic regulation in bovine preimplantation embryos. Using a morphokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Accumulating evidences showed that crosstalk between metabolism and epigenetics plays important roles in gene expression, cell proliferation and cell differentiation [ 56 ], and has been attracting increasing interests in the context of development [ 57 ]. Recently, it was reported that high level of α-Ketoglutarate, an intermediary metabolite in the TCA cycle, regulates DNA methylation/demethylation dynamics through TET activity to promote pluripotency and improve embryonic development [ 58 , 59 ]. Here, we propose that lactate, as an important cellular metabolite, not only provides energy for post-compaction embryonic development [ 25 ], but also regulates dynamics of histone lactylation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences showed that crosstalk between metabolism and epigenetics plays important roles in gene expression, cell proliferation and cell differentiation [ 56 ], and has been attracting increasing interests in the context of development [ 57 ]. Recently, it was reported that high level of α-Ketoglutarate, an intermediary metabolite in the TCA cycle, regulates DNA methylation/demethylation dynamics through TET activity to promote pluripotency and improve embryonic development [ 58 , 59 ]. Here, we propose that lactate, as an important cellular metabolite, not only provides energy for post-compaction embryonic development [ 25 ], but also regulates dynamics of histone lactylation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to DNA demethylation, histone demethylase enzymes also use α-KG as a co-factor to remove methyl groups from histones residues. Although α-KG is crucial for histone demethylation, it has been shown that the accumulation of succinate within the cell may antagonize the activity of histone demethylases and promote cell differentiation from embryonic stem cells ( Carey et al., 2015 ; Ispada et al., 2020 ; TeSlaa et al., 2016 ).
Figure 4 DNA and histone demethylation are controlled by metabolism Connection between metabolism and DNA and histone demethylation of human (purple), mouse (green) and bovine (yellow) in vivo (full lines) and in vitro (dashed lines) pre-implantation stages (MII, 2, 4, 8, 16C/MO and BL).
…”
Section: Resultsmentioning
confidence: 99%
“…The importance of metabolites in regulating the cellular epigenome, inducing long-term changes to the cells, the so-called ‘metaboloepigenetic regulation’, has been reported in different cell types, such as stem cells and tumor cells ( Donohoe and Bultman, 2012 , reviewed by Etchegaray and Mostoslavsky, 2016 ; Reid et al., 2017 ; Van Winkle and Ryznar, 2019 ). More recently, studies have shown that epigenetic reprogramming might also be dependent on the metabolic pattern during the early stages of embryonic development ( Ispada et al., 2020 ; Zhang et al., 2019 ). In this sense, understanding the metaboloepigenetic profile of in vivo embryos and how it differs from in vitro derived embryos in different species is essential to guiding future studies on modifying in vitro culture systems to improve embryo viability and progeny health.…”
Section: Introductionmentioning
confidence: 99%
“…Also, H3K27me3 is generally localized in gene‐rich regions with low DNA methylation and is mostly associated with facultative heterochromatin (Wiles, 2017). In bovine blastocysts, slow embryos show lower levels of H3K9me3 (Ispada, 2021) and DNA methylation than fast embryos (Ispada, 2020). In this manner, methylation of H3K27 might be overrepresent in response to this highly permissive chromatin structure.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo early cleavages have been used as a model to classify and even select mammalian embryos for transfer in the last decades (Basile, 2015; Carrasco, 2017; Dal Canto, 2012; Herrero, 2013; Pribenszky, 2010; Wong, 2010). Studies report that fast and slow developing embryos diverge in terms of metabolism, response to environment and stress, energy production pathways and storage, and epigenetic reprogramming profiles that result in transcription alteration (Annes, 2019; de Lima, 2020; dos‐Santos, 2016; Ispada, 2020; Milazzotto, 2016; Silva, 2016). So far, fast embryos perform better than slow embryos regarding quality parameters (de Lima, 2020).…”
Section: Introductionmentioning
confidence: 99%